Systemic Violations in EU Asylum Law: Cover or Catalyst? - Tsourdi, Evangelia Lilian; Costello, Cathryn (German Law Journal, 2023)
The concept of a systemic fundamental rights violation refers to a particular set of violations that are both widespread and embedded, so their reoccurrence may be assumed to be likely. It takes on at least two distinctive roles in EU asylum law and policy. One role is linked with the functioning of the principle of mutual trust, a principle that obliges Member States to recognise each others' systems and decisions, presuming them to be legal, apart from exceptional cases. In this context, the principle sets the standard from when the presumption of legality is rebutted. In its conceptualisation and application, it is in tension with European human rights law, and, for a period, set up frictions between the CJEU (in NS/ME and Opinion 2/13) and the ECtHR (in MSS and Tarakhel). This tale of judicial frictions is not merely of historical interest. Its legacy is, we conclude, a thin concept of systemic breach, characterised by an over-individualized approach to assessing the human rights risks. The second role for the concept of systemic violations relates to embedded violations, including at the EU's external borders. We demonstrate the utility of this other invocation, in particular as systemic breaches often signal deeper rule of law issues both within particular national systems and embedded within the Common European Asylum System (CEAS). We illustrate that the CEAS itself brings about systemic human rights violations. Identifying and responding to the systemic in asylum increasingly relates to the credibility of the EU as a Union based on the respect for fundamental rights and the rule of law.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Asylum; Court of Justice of the European Union; EU Law; European Court of Human Rights; Fundamental rights; Migration; Non-refoulement; Refugees